Penerapan Kurikulum Merdeka Pada Peserta Didik Kelas 7 dalam Mata Pelajaran Bahasa Bali di SMP Dharma Wiweka Denpasar - Ni Luh Putu Diah Widiastari; Ni Wayan Yuliandewi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The independent curriculum is a curriculum with diverse intracurricular learning where the content is more optimal so that students have enough time to explore concepts and strengthen competencies. In the learning process, the teacher has the flexibility to choose various teaching tools so that learning can be adapted to the learning needs and interests of students. In this curriculum there are projects to strengthen the achievement of the Pancasila student profile. Where developed based on certain themes set by the government. This project does not aim to achieve certain learning achievement targets, so it is not tied to subject content. The essence of this independent curriculum is freedom of learning. This is conceptualized so that students can explore their respective interests and talents. For example, if two children in one family have different interests, then the benchmarks used to judge are not the same. Then children also cannot be forced to learn something they do not like so that it will provide autonomy and independence for students and schools. The main characteristics of this curriculum that supports learning recovery are project-based learning for the development of soft skills and character according to the Pancasila student profile, focusing on essential ministers so that there is sufficient time for in-depth learning for basic competencies such as literacy and numeracy, and flexibility for teachers to perform differentiated learning according to the ability of students and make adjustments to the local context and content. In the current era of industrial revolution 4.0 education, it is more focused on emphasizing technological knowledge by strengthening local content, so that teachers in this era are highly required to be able to master technology that aims to help the learning process. The learning process is emphasized more on the freedom of students to choose, do and understand the learning process. So that all learning in the current era will continue to refer to the profile of Pancasila students, namely faith, fear of God Almighty and noble character; Global diversity; Worked together; Independent; Critical reasoning; as well as creative. This has become the basis for the formation of an independent curriculum which has begun to be implemented at the Driving School and will be distributed equally to other schools. The driving school is a fostered school to realize the vision of Indonesian education in realizing an advanced Indonesia that is sovereign, independent, and has personality through the creation of Pancasila Students.